The Influence of Product Quality, Service Quality and Price on Customer Satisfaction at the Pattallassang Motor Workshop in Takalar Regency - Abd Rahim (Journal GoodWill, 2023)
This research aims to examine the influence of product quality, service quality and price on customer satisfaction at the Pattallassang Motor repair shop. The population in this study are all people who own motorbikes. Using the Maholtra formula, the sample size was determined as 140 respondents. The type of data used is descriptive quantitative obtained from questionnaires distributed to respondents. The research results show that product quality and service quality have a positive and significant influence on customer satisfaction. This indicates that customers tend to be satisfied with the products and services provided by the Pattallassang Motor repair shop. However, price does not have a positive and significant effect on customer satisfaction. This shows that price is not the main factor influencing customer satisfaction at the workshop. Statistical analysis uses the SPSS version 25 application to test the influence of these variables. The results confirm that product quality and service quality have a significant impact in increasing customer satisfaction, while price does not have a significant impact in this regard.